Evaluating the chemical stability of metal oxides in SO3 and applications of SiO2‐based membranes to O2/SO3 separation. Issue 11 (31st May 2019) - Yu, Xin; Meng, Lie; Nagasawa, Hiroki; Kanezashi, Masakoto; Machida, Masato; Tsuru, Toshinori
Abstract: The decomposition of sulfur trioxide to produce sulfur dioxide and oxygen using a catalytic membrane reactor is technology that promises to improve the economic viability of the thermochemical water‐splitting Iodine‐Sulfur (IS) process for large‐scale CO2 ‐free hydrogen production. The chemical stability of membrane materials under SO3, however, is a significant challenge for this strategy. In this study, microporous membranes with a layered structure that consisted of a membrane support prepared from α‐Al2 O3, an intermediate layer prepared from silica‐zirconia, and a top layer prepared from bis (triethoxysilyl)ethane‐derived organosilica sols, were examined for stability under SO3 and for use in SO3 /O2 separation. An α‐Al2 O3 support that features SiO2 –ZrO2 intermediate layers with large pore sizes and a high Si/Zr molar ratio showed excellent resistance to SO3, which was confirmed by N2 adsorption, Energy Dispersive X‐ray Spectroscopy (EDS), and Scanning Electron Microscopy (SEM). These membranes also demonstrated a negligible change in gas permeance before and after SO3 exposure. Subsequently, in binary‐component gas separation at 550°C, microporous organosilica‐derived membranes achieved an O2 /SO3 selectivity of 10 (much higher than the Knudsen selectivity of 1.6) while maintaining a high O2 permeance of 2.5 × 10 −8 mol m –2 s –1 Pa –1 .